Representasi Logika melalui Analisis Sintaksis - Yoga, Adwidya (Research Community for Critical Society and Environment, 2024)
This research was based on the author's concern when he saw that postgraduate student, especially linguistics programs, did not use standard language varieties when corresponding via email. The variety of language used tends to be non-formal and like written spoken language. Departing from this situation, through this research the author aims to trace the syntactic errors in language of postgraduate linguistics program students and identify representations of logical thinking based on this language behavior. This research was studied qualitatively by analyzing data in the form of sentences collected from the contents of email messages from graduate students in linguistics programs. A total of fifteen data were analyzed and various syntactic errors were found which included errors in sentence structure, word use, punctuation use, phrase use and clause use. Word errors rank at the top in this research. The results of this research have implications for the evaluation of the learning process and language learning in higher education in particular, so that students are more sensitive to simple syntactic elements so that simple syntactic errors can be avoided.